Busy Book sebagai Media Pembelajaran yang Menarik dan Menyenangkan pada Anak Usia Dini di Era Society 5.0 - Kholifaturrohmah (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2025)
The rapid changes in science and technology require us to be ready to face world changes, especially in the field of education. Learning media that can be developed to prepare educators to face the challenges of the era of society 5.0 is preparing learning media to carry out new innovations in creating interesting and fun learning media for young children. One of the interesting learning media is busy books. This research aims to determine and describe the form of busy books and the educational value developed in busy books for early childhood games and learning. The method used in this article is the literature study method by obtaining relevant information. The results of the research article show that the use of busy book media is an interesting learning media for young children. media shaped like a book whose main material is made of flannel, has pages and each page contains activities accompanied by pictures and colors that are attractive to children.